Voltammetric, spectroelectrochemical, and electrocatalytic properties of thiol-derivatized phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Voltammetric and spectroelectrochemical properties and electrocatalytic activities of thiol-derivatized phthalocyanine complexes for hydrogen production have been investigated. Voltammetric and spectroelectrochemical measurements show that while cobalt phthalocyanine complexes (CoPc) present well defined metal-based and ring-based redox processes, all other complexes give only ring-based reduction and oxidation processes. The redox processes are generally diffusion-control led, reversible and one-electron transferred processes. The complexes bearing tetra(acetoxyethylthio) substituents represents aggregation tendency in DCM solution. Cobalt and nickel phthalocyanines are easily electrodeposited on the GCE working electrode during the repeating cycles of positive potentials. Electrocatalytic activities of electrodeposited complexes indicated that Cope catalyzed the proton reduction via the electro-reduced [Co'Pc2-](1-) and/or [Co'Pc3-](2-) species depending on the pH of the aqueous solution. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: hydrogen; phthalocyanine; proton reduction; spectroelectrochemistry; chronoamperometry; electrodeposition; electrocatalyst; RECEPTOR FUNCTIONAL PHTHALOCYANINES; ELECTROCHEMICAL CHARACTERIZATION; HYDROGEN-PRODUCTION; SUBSTITUTED COBALT; PROTON REDUCTION; COMPLEXES; ELECTRODE; METALLOPHTHALOCYANINES; THIOPHENES; GRAPHITE